Nepal energy sector assessment, strategy, and road map. (Metro Manila, Philippines Asian Development Bank, 2017)
Nepal is facing an unprecedented energy crisis caused by an acute shortage of power and fuel supply. To improve energy security and stimulate economic growth, the government is accelerating the sustainable development of Nepals hydropower potential. This publication highlights Nepals energy sector performance, major development constraints, and government development plans and strategy. It outlines the future support strategy of the Asian Development Bank (ADB) whose main focus is to make the countrys energy sector a key driver of inclusive economic growth. Linked to ADBs country partnership strategy for Nepal 20132017, this publication provides guidance for future investment and technical assistance operations.
Keywords: Energy policy -- Nepal; Energy Policy, Economics and Management; Electronic books